IMPLEMENTASI METODE BAHTSUL MASA’IL DALAM MENUMBUHKAN CRITICAL THINKING SANTRI PADA MATA PELAJARAN FIKIH DIPONDOK PESANTREN AN NAJAH GONDANG SRAGEN - Imam Shodiq Anshori; Afga Sidiq Rifai (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study explores how the Bahtsul Masa’il method is used to foster critical thinking skills among students (santri) at the AnNajah Gondang Islamic Boarding School, particularly in Fiqh (Islamic jurisprudence) classes. The research is guided by three core questions: why this method was chosen for Fiqh learning, how it supports the development of critical thinking, and what challenges arise during its implementation. Using a qualitative approach, data were collected through observations, indepth interviews, and documentation. The findings show that Bahtsul Masa’il is favored because it encourages students to engage more actively, think critically, and analyze religious issues from both classical and contemporary perspectives. In practice, the method is applied through open discussion forums where students are invited to identify problems, build arguments, and propose solutions based on Islamic legal reasoning. These discussions gradually nurture a more independent and critical way of thinking. However, the implementation is not without challenges. Differences in students’ abilities, limited access to relevant references, the need for skilled moderators, and time constraints during discussions all present obstacles. Still, despite these hurdles, Bahtsul Masa’il remains a powerful tool in shaping students' intellectual character and helping them grow into independent thinkers